Impact of negative word of mouth on consumers’ attitude. Moderating role of advertising under cognitive involvement conditions - Safeena Yaseen; Smith Boonchutima; Ibtesam Mazahir (Cogent Social Sciences)
The proliferation of internet technology and social media platforms has revolutionized consumer-brand interactions, enabling widespread participation in online brand conversations and significantly amplifying the impact of word-of-mouth communication. Therefore, they actively post and increasingly rely on online product reviews, particularly when the reviews are negative. These product reviews carry cognitive and affective information that can be found in comparative and non-comparative formats. In this study, we focused on cognitive information available online in comparative and non-comparative formats. This study examines the impact of negative word-of-mouth communication on consumer attitudes and the moderating role of attribute-based advertising under comparative and non-comparative cognitive involvement conditions. A two cognitive negative word-of-mouth and two cognitive attribute-based advertisement mixed designs were used to empirically test the proposed research model. Data were analyzed using a two-way ANOVA in SPSS to examine the interaction effects between NWOM and advertising formats on consumer attitudes. The findings reveal that attribute-based advertising communication moderates the negative impact of NWOM communication on consumer attitudes under comparative and non-comparative cognitive involvement conditions. The theoretical implications, practical implications, and recommendations are discussed for further research in the field of online media communication.